Gathering evidence on an after-school supplemental instruction program: Design challenges and early findings in light of NCLB. - Chatterji, Madhabi; Kwon, Young Ae; Sng, Clarice (Education Policy Analysis Archives, 2006)
The No Child Left Behind (NCLB) Act of 2001 requires that public schools adopt research-supported programs and practices, with a strong recommendation for randomized controlled trials (RCTs) as the “gold standard” for scientific rigor in empirical research. Within that policy framework, this paper compares the relative utility of federally-recommended RCT versus the demonstrated extended term mixed-method (ETMM) designs as options for monitoring effects of novel programs in real-time field settings. Guided by the program’s theory of action, a year-long, two-phase study was conducted to monitor the context, processes and early outcomes of an after-school supplemental program in a New York elementary school. In both phases, the design combined a matched-groups, quasi-experiment with qualitative classroom observations and descriptive surveys. Early findings showed some positive, albeit “gross” program effects. Although findings are tentative, the ETMM approach enhanced interpretations by shedding light on relevant environmental variables, causes for program instabilities and sample attrition, and factors affecting treatment fidelity and scaling-up of the program beyond the pilot year.